A comprehensive comparative study on the energy application of chars produced from different biomass feedstocks via hydrothermal conversion, pyrolysis, and torrefaction. (15th October 2022) - Güleç, Fatih; Williams, Orla; Kostas, Emily T.; Samson, Abby; Lester, Edward
Highlights: Three different UK-based biomasses were processed in three different thermal conversion technologies. Different biomass feedstocks behave relatively different in thermal conversion technologies. Whitewood based biochars have the greatest potential in the bioenergy application. Seaweed based biochars provide relatively high ash contents minimising the bioenergy application. Abstract: Understanding the suitability of different conversion technologies for different types of biomass feedstocks is crucial in delivering the full valorisation of different types of biomasses. This is novel research which presents an extensive comparative study on how three different thermal conversion technologies (torrefaction, pyrolysis, and semi-continuous hydrothermal conversion) and process interdependencies are influenced by different feedstocks (Rapeseed (RS), Whitewood (WW), Seaweed Laminaria digitata (LD) )) for the optimisation of char (hydrochar/biochar) formation and their associated bioenergy applications. A wide range of processing conditions was analysed to optimise char formation and potential applications of these chars in energy production were extensively investigated. Based on the evaluation of char structures, hydrothermal conversion could be an applicable method for char production from WW and RS. The char yield of WW is in the range of 30–50 wt% at the early stage of hydrothermal carbonisation (HTC, 235 °C). Increasing temperature (>265 °C) decreased char yield but produced a higher HHV char (∼30 kJ/g). Approximately 90 wt% of LD dissolved into the water at low temperatures (<200 °C) during hydrothermal conversion, leaving small amounts of char with a significant ash content (∼50 wt%). During pyrolysis, RS and WW gradually decomposed and produced char with yield of ∼ 35–40 wt% at 400 °C consisting of a high lignin content with a HHV of > 34 kJ/g. Similarly, LD decomposed gradually with a char yield of 45 wt% at 400 °C, but with a low HHV (∼15 kJ/g) and high ash content (20 wt%). WW had relatively high char yield of ∼ 60 wt% during pyrolysis at 250 °C, with a HHV of 25 kJ/g. Although RS had a high char yield (∼75 wt%) with a high HHV (>30 kJ/g), the chars still contained a significant amount of volatiles. The WW char from these three thermal conversion technologies, and RS chars produced by pyrolysis and hydrothermal conversion, could have a potential application in bioenergy production. However, the ash content and low HHV make LD unsuitable for bioenergy applications.